A scoping review of stereotype threat for BIPOC: Cognitive effects and intervention strategies for the field of neuropsychology. Issue 2 (17th February 2022) - VanLandingham, Hannah; Ellison, Rachael L.; Laique, Aamir; Cladek, Andrea; Khan, Humza; Gonzalez, Christopher; Dunn, Megan R.
Abstract: Objective: Abundant evidence documents stereotype threat's (ST) detrimental effect on test performance across identities and contexts (i.e., eliciting underperformance). Review of the literature shows varied aspects of both stereotyped identities and cognition are inconsistently explored across studies. Only a portion of the literature focuses on ST's impact on Black, Indigenous, and People of Color (BIPOC). It is important to understand and learn to mitigate ST, particularly for historically marginalized and systemically oppressed BIPOC patients. Relevance exists for neuropsychologists, who engage in activities (i.e., assessments) that may activate ST, and should be aware of additional factors impacting testing results and clinical decision making. Method: Using scoping review criteria (Peters et al., 2015 ) and Preferred Reporting Item for Systemic Reviews and Meta-Analysis (PRISMA) guidelines, we reviewed literature across multiple databases ( Google Scholar, PubMed, PsychINFO ) on ST and cognition with a focus on BIPOC. Results: The current literature suggests that race-based ST may be implicated in underperformance for executive functioning and separately working memory. There is limited research on the effects of ST for memory, language, attention, and visuospatial skills. Conclusion: Research on ST requires additional attention to establish interventions to mitigate negative effects in practice. These results provide 1) an overview of the cognitive implications of ST, 2) address the scope of this impact for BIPOC, and 3) provide possible intervention and training strategies for neuropsychologists and other clinicians to work to mitigate the effects of ST on BIPOC.